2023
DOI: 10.3390/cancers15061854
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Inflammation and Lung Cancer: Is It a Real Paradigm? Prognostic Value of Inflammatory Indexes in Patients with Resected Non-Small-Cell Lung Cancer

Abstract: Background (1): Our goal was to investigate if and how pre-operative inflammatory status can influence the long-term prognosis of patients undergoing lung surgery for cancer. Materials and Methods (2): This prospective observational study includes the agreement of all operable patients to the study, who were referred to our department between 1 January 2017 and 30 December 2018. The inflammatory pre-operative status of the patients was investigated by calculating albumin, CPR (c-protein reactive), complete blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Meanwhile, SII was also considered to be correlated to unfavorable outcomes of various tumors such as cholangiocarcinoma, lung cancer, gliomas, etc. [ 10 , 21 , 22 ]. Subsequently, there has been an established link between SII and the occurrence and prognosis of chronic heart failure and coronary heart disease [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, SII was also considered to be correlated to unfavorable outcomes of various tumors such as cholangiocarcinoma, lung cancer, gliomas, etc. [ 10 , 21 , 22 ]. Subsequently, there has been an established link between SII and the occurrence and prognosis of chronic heart failure and coronary heart disease [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, high levels of hemoglobin and albumin are positively correlated with the prognosis of NSCLC. 40 Therefore, further investigation has been carried out in this study on whether MAR and NPHR levels could be used as potential biomarkers to predict the disease progression of NSCLC. Interestingly, the results showed that MAR and NPHR were both significantly associated with tumor size, lymph node metastasis, and distant metastasis, which might be a partial suggestion to tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the above, new prognostic tools such as pre-operative NLR, LMR, and the platelet to lymphocyte ratio (PLR) started to be used, achieving a strong correlation with all lung and other types of cancer prognosis [8,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, many hematological markers, which can be easily obtained in daily clinical practice, are increasingly utilized for the prognosis of several cancers, including NSCLC. In particular, systemic inflammation and nutritional status have been proven to be involved in cancer development [8,9], and related biomarkers have been evaluated as possible indicators of outcomes for oncologic patients [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%